1985
DOI: 10.1128/iai.49.1.212-218.1985
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of dialysate-elicited and resident human peritoneal macrophages

Abstract: Recent studies of the antimicrobial capacity of peritoneal macrophages (PM4+) isolated from patients undergoing chronic peritoneal dialysis have raised the question of whether these cells might be analogous to stimulated or activated murine PM+. To explore this possibility, we compared PM+ from these patients (dialysate-elicited PM+) with PM4 obtained from women undergoing laparoscopy (resident PM4) in several in vitro assays of phagocyte function. Although bacterial phagocytosis by cells from both groups of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In contrast, peritoneal maerophages from CAPD patients showed an increased antigcn-presenling eapaeity. This tinding suggests functional aetivation of the peritoneal macrophages by the CAPD treatment, as has also been reported in other studies [25,26]. Data from this study indicated that CAPD peritoneal dendritic cells are capable of inducing both a primary and secondary Tcell response at a similar level to control peritoneal DC, In addition, the antigen-presenting capacity ofthe peritoneal maerophages was increased.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, peritoneal maerophages from CAPD patients showed an increased antigcn-presenling eapaeity. This tinding suggests functional aetivation of the peritoneal macrophages by the CAPD treatment, as has also been reported in other studies [25,26]. Data from this study indicated that CAPD peritoneal dendritic cells are capable of inducing both a primary and secondary Tcell response at a similar level to control peritoneal DC, In addition, the antigen-presenting capacity ofthe peritoneal maerophages was increased.…”
Section: Discussionsupporting
confidence: 88%
“…This conclusion was indicated by the meager luminol-enhanced CL responses and the inability of catalase, azide, or DMSO to inhibit killing. Although the H202-MPO-halide system is effective in killing B. dermatitidis (6,17), resident peritoneal macrophages are noted for their paucity of MPO (14), and this fact probably accounts for our findings. We speculate that activated macrophages could kill B. dermatitidis by an enhanced ability to discharge (degranulate) lysosomal contents (e.g., cationic proteins [16]) into the B. dermatitidis-macrophage interface.…”
mentioning
confidence: 58%
“…CAPD peritoneal cells have features of both immaturity and activation compared to control cells (24). This is particularly true for peritoneal macrophages, which have been reported to be relatively immature cells (6,25), while characteristics such as increased respiratory burst activity and killing of Candida albicans blastophores suggest that they are functionally activated (26,27). We have previously shown that transmigration of monocytes into the peritoneal cavity during the noninfected steady state implies a selective upregulation of functional receptors, preferentially related to adhesion and antigen presentation (19).…”
Section: Discussionmentioning
confidence: 99%